Salicylic acid-mitigates abiotic stress tolerance via altering defense mechanisms in Brassica napus (L.) - Ali, Essa; Hussain, Sayed; Jalal, Fazal; Khan, Muhammad Ali; Imtiaz, Muhammad; Said, Fazal; Ismail, Muhammad; Khan, Salman; Ali, Hayssam M.; Hatamleh, Ashraf Atef; Al-Dosary, Munirah Abdullah; Mosa, Walid F. A.; et al. (Frontiers in Plant Science, 2023)
Under the changing climate due to global warming, various abiotic stresses including drought (D) and salinity (S) are expected to further trigger their devastating effects on the already vulnerable crop production systems. This experiment was designed to unravel and quantify the potential role of exogenous application of salicylic acid (SA) in mitigating both D and S stresses and their combination (D+S), with three replications using CRD (Completely Randomized Design). The obtained results of the current study demonstrated significant effects of all three types of stresses (D, S, and D+S) on various parameters in Brassica napus plants. Quantifying these parameters provides a more informative and precise understanding of the findings. Current results revealed that all three stress types (D, S, and D+S) resulted in a reduction in leaf area (13.65 to 21.87%), chlorophyll levels (30 to 50%), gaseous exchange rate (30 to 54%) and the concentration of mineral ions compared to non-stressed plants. However, application of SA helped in mitigating these stresses by ameliorating the negative effects of these stresses. Moreover, Malondialdehyde (MDA) contents, an indicator of lipid per-oxidation and oxidative stress, the levels of antioxidants, proline content, an osmolyte associated with stress tolerance, and sugar content in the leaves were elevated in response to all stress conditions. In addition, the ultra-structures within the leaves were negatively affected by the stresses, while an application of SA considerably minimized the deterioration of these structures thus providing protection to the brassica plants against the stresses. In a nutshell, the findings of this study suggest that SA application in S, D and S+ D stresses provides evasion to the plants by improving different physiological and growth indices. The application of Salicylic Acid (SA) mitigated the negative effects of the stresses on all the above parameters, reducing MDA contents (47%), antioxidants (11 to 20%), proline (28%), sugar contents (20.50%), and minimizing the deterioration of ultra-structures. The findings emphasize the potential mitigatory role of SA in mitigating D and S stresses and highlight the need for further research to understand the underlying mechanisms in detail and explore its practical application in farming practices.